Transcatheter closure of atrial septal defect in a patient with Noonan syndrome after corrective surgery - Mangovski, Ljupčo; Farkić, Mihajlo; Jovović, Ljiljana (Vojnosanitetski pregled, 2015)
Introduction. Transcatheter atrial septal defect (ASD) closure is considered to be a gold standard for patients with the suitable anatomy as compared to cardiac surgery. Reocurrence of ASD after surgical closure is a very rare late complication which can be successfully managed with transcatheter procedure. Case report. We reported a female patient with Noonan syndrome who presented with hemodinamically significant ASD 37 years after the corrective cardiac surgery. Due to numerous comorbidities which included severe kyphoscoliosis, pectus excavatum and multiple surgeries we decided to perform transcatheter closure of ASD. The procedure itself was very challenging due to the patient’s short stature and heart’s orientation in the chest, but was performed successfully. The subsequent follow-up was uneventful and the patient reported improvement in the symptoms. Conclusion. Transcatheter closure of ASD in a patient with Noonan syndrome with the history of surgically corrected ASD can be performed successfully, despite challenging chest anatomy.
Keywords: noonan syndrome; heart septal defects; congenital abnormalities; cardiovascular surgical procedures; treatment outcome